Brain Rot and Focus Disorders Survey Impact of Consumption of TikTok and Instagram Reels Content on Teenagers - Harsanto, Eka; Yunike, Yunike; Kusumawaty, Ira (International Journal Scientific and Professional, 2025)
This study investigates the impact of short-form video content consumption on adolescents’ cognitive health, particularly focusing on symptoms of brain fog and attention disorders. Conducted through a quantitative survey involving adolescents aged 16 to 21, the research measured daily usage of TikTok and Instagram Reels and its correlation with self-reported cognitive symptoms. The results indicate a strong positive association between excessive use of these platforms and the prevalence of focus problems and mental fatigue. Interestingly, adolescents with moderate usage reported fewer cognitive complaints, suggesting that limited exposure may offer a form of cognitive stimulation. These findings support existing concerns about digital media overload while also proposing a new perspective through the "Optimal Digital Stimulation" theory. The study highlights the importance of digital balance and offers implications for educational interventions and policy development aimed at promoting healthy media consumption among youth.